SPORTS MEDIA AND ITS ROLE IN PROTECTING STUDENTS OF THE COLLEGE OF PHYSICAL EDUCATION AND SPORTS SCIENCES AT THI QAR UNIVERSITY FROM INTELLECTUAL DEVIATIONS - Lecturer Dr. Ahmed Saad Abdulrazzaq (Proximus Journal Publishing, 2024)
The widespread spread of media and the emergence of new, more advanced means of communication have advanced a lot, which has made many people wonder about the role that they have become able to achieve these goals in social life, and their extent on the ideas, values, trends and behaviors of people in general and the youth category in particular, as these means facilitate communication and contact between people and societies, and since that time, they have made the world a single global village in which time and space are facilitated
Keywords: Sports media; intellectual deviations; College of Physical Education